2021
DOI: 10.3390/earth2010008
|View full text |Cite
|
Sign up to set email alerts
|

The Severity of Environmental Pollution in the Developing Countries and Its Remedial Measures

Abstract: Environmental pollution has a great impact on human health, ecosystems, and financial development. This paper depicts the recent studies on the severity of environmental pollution in developing countries. Its remedial measures were based on a questionnaire survey in the polluted sites, which collected data and information on the types, causes, effects, sources, and duration of environmental pollution, obtained from available publications and newspaper information reported in recent years. A total of 400 respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…As a result, many signi cant infrastructure projects, like roads, rail, bridges, and large buildings, have been undertaken. These projects have led to environmental degradation, dust production, and displacement of communities without proper safety and environmental precautions (Nahar et al, 2021). The road dust and soil dust from these construction projects are signi cant contributors to air pollutants, especially PM, during the dry season (DOE, 2018, 2019).…”
Section: Power Plantsmentioning
confidence: 99%
“…As a result, many signi cant infrastructure projects, like roads, rail, bridges, and large buildings, have been undertaken. These projects have led to environmental degradation, dust production, and displacement of communities without proper safety and environmental precautions (Nahar et al, 2021). The road dust and soil dust from these construction projects are signi cant contributors to air pollutants, especially PM, during the dry season (DOE, 2018, 2019).…”
Section: Power Plantsmentioning
confidence: 99%
“…With rapid industrialization, population growth, and vehicular activities, South Asian cities have become the major hotspots of PM emissions (Rahman et al 2021). These increasing air pollution pressures are leading to environmental risks as well as human health risks that will cost $8.1 trillion worldwide in 2019, equivalent to 6.1% of world GDP (Nahar et al 2021). Thus, it is important to monitor the spatiotemporal variations in air pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…As per the literature, the prominent causes identified for high pollution in and around the city were vehicular emissions, bio-fuel burning for domestic and industrial purposes, and brick kilns (Begum and Hopke 2018). Before 1999, relatively inadequate and ineffective attempts were made to control and regulate industrial and vehicular emissions, with limited success in administrative efforts to mitigate air pollution (Nahar et al 2021). Different long-and short-term studies (Begum and Hopke 2018;Islam et al 2020;Rahman et al 2020) have reported that unplanned urbanization in Dhaka to accommodate the huge population and the above-mentioned causes of air pollution have increased PM 2.5 and PM 10 concentrations with very high toxicity potential values (Zaman et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The need for environmental knowledge and knowledge of the extant policies as well as sustainability actions cannot be over emphasized in view of the value of such to healthy living and sustainable development. Equally, the negative implication of unhealthy environment has over the time surfaced among different populations world over warranting, the aspiration for environmental sustainability [2][3][4][5][6][7]. The symbiotic relationship between the natural environment and man, which reinforce the healthiness of the natural environment as well as the carrying capacity to sustain man, has been certified through empirical substantiation as the unseen conduit for sustainability [8].…”
Section: Introductionmentioning
confidence: 99%